Outside the box : rethinking ADD/ADHD in children and adults : a practical guide - Brown, Thomas E., 1942- (American Psychiatric Association Publishing, 2017)
The book is written in an accessible, even entertaining, way that provides science-based answers to a wide variety of questions about ADHD, its evaluation, and treatment.